Using social media as organizational memory consolidation mechanism according to attention based view theory - Barros, Victor Freitas Azeredo (2015)
Increasingly, organizations are aware that the knowledge generated in organization is a primary factor to remain competitive in the market. The Organizational Memory (OM) conceptualizing how the process of creation, storage and dissemination of knowledge over time can influence the actions and decisions of the organization. For this, it is necessary that the attention of individuals to be targeted and aligned, noticing the stimuli from the environment, and directing the time and cognitive effort towards the decisions to be made in the organization. This scenario, the paper provides a discussion of 22 case studies found in literature that were analyzed using the Attention-Based View of the Firm as a guiding lens. This analysis shows some evidence and relevant implications of the use of Social Media in the organizational context as well as a first theoretical description of how the focus of attention of decision makers influence the development of OM.